PENDUGAAN VOLUME TEGAKAN BERDASARKAN JUMLAH DAN KERAPATAN TAJUK PADA FOTO UDARA - Ishak Sumantri; Haryono Haryono; Machfudh Machfudh (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
The relationship of stumpage volume by crown densities persentage and numbers of crown which measured on aerial photos are the object of this study. Research take place in tropical rain forest which have been harvested by Indonesia Selective Cutting (TPI) in East Kalimantan. Result of model analysis are :1. The distribution of crown densities percentage and numbers of crown data are normal distribution.2. The relationship of stumpage volume over crown densities percentage and numbers of crown data are :V = -169. 7132 + 3.8514 N + 2.8532C + 0.0004C2 + 0.014CNwhere : V : stumpage volume (m3) N : Numbers of crown C : Crown densities percentage.Coeficient of determination of the relation (R) = 0. 7828. This model is significant at 95 % level after tested by F- test.3. The model and its analysis can be taken in east Kalimantan only.